2012
DOI: 10.1021/nn203586j
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Gold Nanorods by a Stochastic “Popcorn” Mechanism

Abstract: Gold nanorods have significant technological potential and are of broad interest to the nanotechnology community. The discovery of the seeded, wet-chemical synthetic process to produce them may be regarded as a landmark in the control of metal nanoparticle shape. However, the mechanism by which the initial spherical gold seeds acquire anisotropy is a critical, yet poorly understood, factor. Here we examine the very early stages of rod growth using a combination of techniques including cryogenic transmission el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
183
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(201 citation statements)
references
References 68 publications
18
183
0
Order By: Relevance
“…Optical properties of gold nanorods have been reported by Edgar et al 38) Gold nanorods showed two surface plasmon bands in visible and NIR regions 29) (Fig. 3).…”
Section: Stimuli-responsive Systems Of Therapeuticsmentioning
confidence: 57%
See 2 more Smart Citations
“…Optical properties of gold nanorods have been reported by Edgar et al 38) Gold nanorods showed two surface plasmon bands in visible and NIR regions 29) (Fig. 3).…”
Section: Stimuli-responsive Systems Of Therapeuticsmentioning
confidence: 57%
“…33,34) Other "replacement" reactions may include thiol groups to gold nanorods. [35][36][37][38][39] Moreover, gold nanorods can be modified with a silica shell following attachment of desired molecules.…”
Section: Stimuli-responsive Systems Of Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,[17][18][19] While the aspect ratios of Au NRs can be fine-tuned by simply varying the concentration of Ag + ions in the growth solution, the exact roles that Ag + ions play in the symmetrybreaking of the isotropic seeds and the subsequent anisotropic NR growth still remain elusive and controversial. 36,[47][48][49][50] In striking contrast to the excellent control over NR aspect ratios, limited success has been achieved so far in the precise facet control of NRs using the seed-mediated growth method.…”
Section: Introductionmentioning
confidence: 99%
“…However, improvements in the quality of the chemical seeding methods since 2004 have eroded the advantage of the photochemical method. 3943 Recently, detailed mechanisms of nanorod formation were discussed, 44,45 revealing that chemical seeding methods have the potential to form more uniform, reproducible, and shape-controlled gold nanorods.…”
Section: Introductionmentioning
confidence: 99%